Extremal optimisation approach to joint routing and scheduling for industrial wireless networks. (2016) - He, Zhidong
Industrial wireless networks (IWNs), different from ad hoc and traditional mesh networks, feature in centralised management architecture and energy-limited devices. In this paper, we propose a technique based on extremal optimisation (EO) approach to solve the joint routing and link scheduling problem in IWNs. After analysing the feasibility of cross-layer optimisation in IWNs, an integer linear programming (ILP) problem in accordance with the characteristics of IWNs, is presented to optimise the real-time performance and the network lifetime. Further, EO is investigated to solve the ILP model, where the fitness assignment strategy, mutation rules and operating process are designed. To our knowledge, it's the first time that EO is applied for scheduling problem in wireless networks. Numerical results show that our approach can achieve real-time communication with improved latency and optimal network lifetime with balanced energy consumption among nodes. And the trade-off between energy consumption and path delay is further demonstrated.